Prospect of low-cost energy conservation in residential energy consumption - Ruchi Tyagi; Suresh Vishwakarma (Institute of Advanced Engineering and Science, 2021)
The energy sector of trinidad and tobago (T&T), with its nationally determined contributions (NDCs), is still struggling for its place in mainstream academic literature. The review paper aims to identify the prospects of low-cost energy conservation measures in the residential sector of T&T. The review follows a four-step review methodology to serve as a basis for creating policy and practice guidelines. First, review articles are checked for their quality on a 5-point scale on the mixed methods appraisal tool (MMAT) to check the quality of review articles. Second, Microsoft Excel, R (RQDA) package, and Voyant tools have been used to index code, analyse, and visualise data. The research trends on small islands developing states (SIDS) energy aspect in general and T&T specifically highlight the critical role of energy challenges related to economic and social development, emphasising technology, infrastructure development, and funds availability. Awareness of low-cost energy conservation measures has a high prospect in reducing residential consumption and balancing demand-side management. This paper contributes to facilitating policy direction on energy efficiency and energy conservation for T&T and other SIDS.